Bioanalytical Method Validation of Metformin Hydrochloride in Human Plasma by HPLC-UV for Preliminary Population-Based Pharmacokinetic Modeling Study - Erna Kristin; Akhmad Kharis Nugroho; Dwi Aris Agung Nugrahaningsih; Mustofa Mustofa; Ari Wibowo; Dimas Adhi Pradana (Universitas Gadjah Mada, 2023)
This study aims to validate the method for measuring metformin hydrochloride plasma concentrations using High-Performance Liquid Chromatography (HPLC). This research performed chromatography on a 250 mm 4.6 mm 5 µm purosphere® Star RP-18 column at ambient temperature with a UV detector system at 233 nm. The mobile phase components were 70% phosphate buffer (KH2PO4) (10 mM), sodium dodecyl sulfate (0.3 mM), and 30% acetonitrile. It was pumped at an isocratic flow rate of 1.2 mL/min. Metformin HCl and ranitidine HCl (internal standard) were extracted using acetonitrile. The calibration curve was linear (R2 = 0.9998) in the 0.18–6 µg/mL concentration range. The lower limit of quantification (LLOQ) was 0.18 µg/mL. For intraday accuracy and precision, the percent difference and the coefficient of variation were less than 4 and 7%, and for inter-day were lower than 8 and 6%. The recovery average was 100.96%. The short-term plasma stability test was stable at 24 h at ambient temperature, and the long-term stability test was steady for 30 d at −20 °C. It was also stable after three freeze-thaw cycles. The method meets selectivity, sensitivity, linearity, accuracy, precision, recovery, carryover, and stability requirements and can be applied to population-based pharmacokinetic modeling.